Planificación estratégica de una empresa consultora "global consult" - Salazar Ledesma, Fidel Mauricio (2010)
The phenomenon of globalization has accelerated the processes of change, so often be identified competencies and capabilities of enterprises to adapt to changing macroeconomic environments and meet the requirements of national and international markets with products and services of high quality, affordable competitive. Consistent with this reality, it identified the need for a Strategic Plan launched a consulting firm that provides the necessary inputs to establish a development plan that enables the institution to sustained orderly growth for the next five years. It should be noted that the Strategic Planning is a discipline that is to identify as clearly as possible the elements of corporate strategy, starting with the fundamental principles and corporate values, Vision and Mission statement, the major objectives, policies, strategies, programs and investment projects. Strategic Planning uses several tools to achieve your goals, based on an assessment of the current situation assessment and projections, analysis of social, economic and political systems and the internal capabilities of the organization. This clarification process rests solidly on the concepts of focus and flexibility, identifying key success factors (CSFs) of the emerging strategy and then deploy the strategic role in a performance management framework by clearly marked.